Fatty Acid Uptake in Liver Hepatocytes Induces Relocalization and Sequestration of Intracellular Copper - Harder, Nathaniel H. O.; Lee, Hannah P.; Flood, Valerie J.; San Juan, Jessica A.; Gillette, Skyler K.; Heffern, Marie C. (Frontiers in Molecular Biosciences, 2022)
Copper is an essential metal micronutrient with biological roles from energy metabolism to cell signaling. Recent studies have shown that copper regulation is altered by fat accumulation in both rodent and cell models with phenotypes consistent with copper deficiency, including the elevated expression of the copper transporter, ATP7B. This study examines the changes in the copper trafficking mechanisms of liver cells exposed to excess fatty acids. Fatty acid uptake was induced in liver hepatocarcinoma cells, HepG2, by treatment with the saturated fatty acid, palmitic acid. Changes in chaperones, transporters, and chelators demonstrate an initial state of copper overload in the cell that, over time, shifts to a state of copper deficiency. This deficiency is due to sequestration of copper both into the membrane bound copper protein, hephaestin, as well as lysosomal units. These changes are independent of changes in copper concentration, supporting perturbations in copper localization at the subcellular level. We hypothesize that fat accumulation triggers an initial copper miscompartmentalization within the cell, due to disruptions in mitochondrial copper balance, that induces a homeostatic response to cytosolic copper overload. This leads the cell to activate copper export and sequestering mechanisms that in turn induces a condition of cytosolic copper deficiency. Taken together, this work provides molecular insight underlying previously observed phenotypes in clinical and rodent models linking copper-deficient states to obesity-associated disorders.